MODULATION OF TGF-β SIGNALING BY PROINFLAMMATORY CYTOKINES IN ARTICULAR CHONDROCYTES - Roman-Blas, Jorge A. (2007)
OBJECTIVE: The normal structure and function of articular cartilage is the result of a precisely balanced interaction between anabolic and catabolic processes. The TGF-β family of growth factors generally exerts an anabolic or repair response; in contrast, proinflammatory cytokines such as IL-1β and TNF-α exert a strong catabolic effect. Recent evidence has shown that IL-1β, and TNF-α, and the TGF-β signaling pathways share an antagonistic relationship. The aim of this study was to determine whether the modulation of the response of articular chondrocytes to TGF-β by IL-1β or TNF-α signaling pathways occurs through regulation of activity and availability of Smad proteins. METHODS: Human articular chondrocytes isolated from knee joints from patients with osteoarthritis (OA) or normal bovine chondrocytes were cultured in suspension in polyHEMA-coated dishes with either 10% FBS media or serum-deprived media six hours before treatment with IL-1β alone, TNF-α alone or IL-1β followed by TGF-β. Nuclear extracts were examined by electrophoretic mobility shift assays (EMSA) for NF-κB and Smad3/4 DNA binding. Nuclear extracts were also subjected to the TranSignal Protein/DNA array (Panomics, Redwood City, CA) enabling the simultaneous semiquantitative assessment of DNA-binding activity of 54 different transcription factors. Nuclear phospho-Smad2/3 and total Smad7 protein expression in whole cell lysates were studied by Western blot. Cytoplasmic Smad7, COL2A1, aggrecan and SOX9 mRNA expression was measured by real-time PCR. RESULTS: The DNA-binding activity of Smad3/4 in the TranSignal Protein/DNA array was down-regulated by TNF-α (46%) or IL-1β treatment (42%). EMSA analysis showed a consistent reduction in Smad 3/4 DNA-binding activity in human articular chondrocytes treated with IL-1β or TNF-α. TGF-β-induced Smad3/4 DNA-binding activity and Smad2/3 phosphorylation were also reduced following pre-treatment with IL-1β in human OA and bovine chondrocytes. Real-Time PCR and Western blot analysis showed that IL-1β partially reversed the TGF-β stimulation of Smad7 mRNA and protein levels in TGF-β-treated human OA cells. In contrast, TGF-β-stimulated COL2A1, aggrecan, and SOX9 mRNA levels were abrogated by IL-1β. CONCLUSIONS: IL-1β or TNF-α exerted a suppressive effect on Smad3/4 DNA-binding activity in human articular chondrocytes, as well, as on TGF-β-induced stimulation of Smad3/4 DNA-binding activity and Smad 2/3 phosphorylation in human OA and bovine articular chondrocytes. IL-1β partially reversed the increase in TGF-β-stimulated Smad7 mRNA or protein levels suggesting that Smad7 may not be involved in the suppression of TGF-β signaling induced by IL-1β or TNF-α in articular chondrocytes. The balance between the IL-1β or TNF-α and the TGF-β signaling pathways is crucial for maintenance of articular cartilage homeostasis and its disruption likely plays a substantial role in the pathogenesis of OA.